2017
DOI: 10.1007/s11912-017-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telemedicine in Providing Thoracic Oncology Care to Remote Areas of British Columbia

Abstract: The Interior Health Thoracic Surgical Group (IHTSG) uses telemedicine, through Virtual Thoracic Surgical Clinics (VTSC), to provide service to remote patients. The IHTSG serves a population of 1.01 million people over an area of 807,538 km (1.3 persons/km) in the Interior and North of British Columbia, Canada. Between 2003 and 2015, the IHTSG conducted 15,073 telemedicine patient encounters at 63 geographic sites. Telemedicine saved these patients a total travel distance of 11.5 million km-an average of 766 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…Interestingly, patients in both groups felt that physical examination was not important for their consultation, which is in contrast to other studies where a lack of physical examination was cited as a concern among patients [17]. Humer et al [31] pointed out that the patient perceived the importance of physical examination may be overstated. An interesting perspective on physical examination is that it has become a ritual done to satisfy the basic needs of patients to feel cared for and for physicians to feel like their work is meaningful [32].…”
Section: Principal Findingscontrasting
confidence: 59%
“…Interestingly, patients in both groups felt that physical examination was not important for their consultation, which is in contrast to other studies where a lack of physical examination was cited as a concern among patients [17]. Humer et al [31] pointed out that the patient perceived the importance of physical examination may be overstated. An interesting perspective on physical examination is that it has become a ritual done to satisfy the basic needs of patients to feel cared for and for physicians to feel like their work is meaningful [32].…”
Section: Principal Findingscontrasting
confidence: 59%
“…A valuable purpose of telehealth may be to support patients who are living remotely or can remain in their own home with additional care supports, and telehealth has been shown to reduce travel time and costs for patients in these settings for other conditions. 22 Only one study in our review measured patient satisfaction with telehealth 13 and reported high levels of satisfaction. Evaluations of telehealth in other fields have reported an equal level of overall satisfaction between telehealth and traditional care and further reported greater satisfaction for telehealth in the domains of convenience and accessibility, suggesting that some, but not all, aspects of patient experience could be enhanced through telehealth.…”
Section: Commentary On Findings: Implications and Applicationsmentioning
confidence: 96%
“…The telemedicine platform provides virtual communication, bridging health services and medical care disparities among select patient populations. The use of telemedicine has expanded in the practice of family medicine [1,2] and primary care [3] and has been accredited with favorable results concerning patients' preferences [4][5][6] and costeffectiveness [7,8]. Among health care centers worldwide, telemedicine may refer to telephone, computer-based audio encounters, mobile phone video applications, and remote symptom and vitals reporting transmitting health care information to the treating physician.…”
Section: Introductionmentioning
confidence: 99%